Pengaruh Faktor Motivasi Push dan Pull Terhadap Keputusan Berkunjung Generasi Z di Chinese Cultural Event Kota Medan - Situmorang, Chelsea Greeny F.; Manurung, John Sihar (Civiliza Publishing, 2024)
In the context of motivation, there are two main elements analyzed, namely internal factors that are pushing factors and external factors that are pulling factors. The combination of these factors influences an individual's decision to attend an event. This research aims to determine the influence of push motivational factors and pull motivational factors on the visiting decision of generation Z at the Chinese Cultural Event in Medan City, particularly the Chinese New Year Festival. The independent variables studied are push motivational factors and pull motivational factors, while the dependent variable is the visiting decision. This research employs a quantitative method with data collected through questionnaires distributed to 90 respondents who visited the Chinese New Year Festival 2024 at W.R. Supratman 2 Medan Senior High School. Hypothesis testing in this research utilizes a multiple linear regression model with partial tests, simultaneous tests, and coefficients of determination, supported by the SPSS 27 program. The results of the research prove that push motivational factors and pull motivational factors partially have a positive and significant effect on the visiting decisions. Simultaneously, both types of motivational factors collectively have a positive and significant effect on the visiting decisions.